Interpreting psychological warfare: understanding religious extremism from a discourse analysis approach / Ahmad Sauffiyan Abu Hasan - Abu Hasan, Ahmad Sauffiyan (2015)
This thesis investigates the meaning of "psychology" in psychological warfare by explaining the factors that permit the existence of religious extremist behavior. Such attention are been given because the problem is relatively understudied in Malaysia and that has resulted in the inability to develop an ideal psychological warfare model to deal with the problem. Since 2001, Malaysia has been labeled as a breeding ground for religious extremist leaders. The recurring number of religious extremist cases magnifies our limited understanding on the psychological context of the problem and if left unattained, can prolong the situation. To propose a theoretical solution to the problem, three research objectives were formulated and they are: (1) how existential psychology can be used to explain religious extremism, (2) how behavioral psychology can be used to explain religious extremism and (3) how psychoanalytical psychology can be used to explain religious extremism. Conclusively, discourse analysis on 37 psychological constructs extracted from three psychological paradigms of Frankl, Pavlov & Skinner, and Freud have enabled this study to theorize a multi-factor stand to look at the problem, hence confirming the root cause of it. Some "Enabling Factors" emerged to authenticate the conceptual model in terms of framing the roots and types of religious extremist behavior. These "Enabling Factors" are divided into three categories consist of Single-Psychological Factor, Double-Psychological Factor, and Triple-Psychological Factor. The results show, religious extremist behavior falls in the Triple-Psychological Factor category. This means, in order for religious extremist behavior to emerge, there must be simultaneous psychological problem of (1) severe inability to develop meaning to life, (2) prolonged environmental stimulation toward aggressiveness and violent, and (3) inability to adopt mature defense mechanisms due to the development of fixation, blind obsession in ritual practice and condoning a destructive worldview towards life. In summary, overcoming these enabling factors is a highly recommended psychological warfare skill in an attempt to understand religious extremism and to halt the problem before it begins. This is a small but significant breakthrough in psychological warfare research as this conceptual model offers a new approach to the prevention of extremist behavior by providing in-depth psychological knowledge on the root causes of the problem and subsequently weaponized psychological warfare initiative for peace purposes.